CDPK2A and CDPK1 form a signaling module upstream of Toxoplasma motility - Emily Shortt; Caroline G. Hackett; Rachel V. Stadler; Robyn S. Kent; Alice L. Herneisen; Gary E. Ward; Sebastian Lourido (mBio, 2023)
ABSTRACT In apicomplexan parasites, the transition between replication and dissemination is regulated by fluctuations in cytosolic calcium concentrations, transduced in part by calcium-dependent protein kinases (CDPKs). We examined the role of CDPK2A in the lytic cycle of Toxoplasma, analyzing its role in the regulation of cellular processes associated with parasite motility. We used chemical-genetic approaches and conditional depletion to determine that CDPK2A contributes to the initiation of parasite motility through microneme discharge. We demonstrate that the N-terminal extension of CDPK2A is necessary for the protein’s function. Conditional depletion revealed an epistatic interaction between CDPK2A and CDPK1, suggesting that the two kinases work together to mediate motility in response to certain stimuli. This signaling module appears distinct from that of CDPK3 and protein kinase G, which also control egress. CDPK2A is revealed as an important regulator of the Toxoplasma kinetic phase, linked to other kinases that govern this critical transition. Our work uncovers extensive interconnectedness between the signaling pathways that regulate parasite motility. IMPORTANCE This work uncovers interactions between various signaling pathways that govern Toxoplasma gondii egress. Specifically, we compare the function of three canonical calcium-dependent protein kinases (CDPKs) using chemical-genetic and conditional-depletion approaches. We describe the function of a previously uncharacterized CDPK, CDPK2A, in the Toxoplasma lytic cycle, demonstrating that it contributes to parasite fitness through regulation of microneme discharge, gliding motility, and egress from infected host cells. Comparison of analog-sensitive kinase alleles and conditionally depleted alleles uncovered epistasis between CDPK2A and CDPK1, implying a partial functional redundancy. Understanding the topology of signaling pathways underlying key events in the parasite life cycle can aid in efforts targeting kinases for anti-parasitic therapies.